Production Of Acetic Acid From Ethanol By Electrolysis (Electrosynthesis) - Riyanto Riyanto (Faculty of Industrial Technology Universitas Islam Indonesia, 2005)
Production of acetic acid from ethanol by electrolysis (electrosynthesis) in alkaline (0.008 M KOH) and acidic (0.08 M HClO4) mediums has been carried out using platinum wire electrode. Besides that, the electrochemical study by cyclic voltammetry (CV) in different scan rates and electrolyte (alkaline and acidic mediums) also had been done. The study shows that the oxidation potential of ethanol ranges from 600-1065 mV in 0.008 M KOH and 700-1125 mV in 0.08 M HClO4. The electrooxidation products were analyzed using the High Performance Liquid Chromatography (HPLC). Keywords: Ethanol, acetic acid, electrolysis, electrosynthesis.